Keeping Up with Phosphorus Dynamics: Overdue Conceptual Changes in Vegetative Filter Strip Research and Management - Ramler, David; Stutter, Marc; Weigelhofer, Gabriele; Quinton, John N.; Hood-Nowotny, Rebecca; Strauss, Peter (Frontiers in Environmental Science, 2022)
Vegetative filter strips (VFS) are best management practices with the primary aim of protecting surface waters from eutrophication resulting from excess nutrient inputs from agricultural sources. However, we argue that there is a substantial time and knowledge lag from the science underpinning VFS to policy and implementation. Focussing on phosphorus (P), we strive to introduce a holistic view on VFS that accounts for the whole functional soil volume, temporal and seasonal effects, the geospatial context, the climatic and physico-chemical basic conditions, and the intricate bio-geochemical processes that govern nutrient retention, transformation, and transport. Specifically, we suggest a step-wise approach to custom VFS designs that links and matches the incoming P from event to multi-annual timescales from the short- and mid-term processes of P retention in the effective soil volume and to the longer-term P retention and offtake coupled to the soil-vegetation system. An a priori assessment of the P export potential should be followed by bespoke VFS designs, in line with local conditions and socio-economic and ecological constraints. To cope with increasingly nutrient saturated or functionally insufficient VFS installed over the last decades, concepts and management strategies need to encompass the transition in understanding of VFS as simple nutrient containers to multifunctional buffer zones that have a complex inner life. We need to address these associated emerging challenges and integrate their implications more thoroughly into VFS research, monitoring, policy, and implementation than ever before. Only then we may get VFS that are effective, sustainable, and persistent.